Modern multidimensional scaling theory and applications - Borg Ingwer; Groenen Patrick J F (New York Springer-Verlag, 2005)
The book provides a comprehensive treatment of multidimensional scaling (MDS), a family of statistical techniques for analyzing the structure of (dis)similarity data. Such data are widespread, including, for example, intercorrelations of survey items, di
Keywords: Data analysis; Multidimensional scaling